Handbook of Comparative Studies on Community Colleges and Global Counterparts (Springer International Handbooks of Education,, 2018)
This book explores the complexities of community colleges and global counterparts by focusing on critical analysis of governance, leadership, and mission. These complexities represent emerging and evolving phenomena that impact the institutions' ability to a) serve students; b) offer sound curricula; c) admit and retain students; d) increase completion rates; e) create viable and sustained partnerships locally and internationally; f) address the needs of unique populations; g) funding and sustainability, and h) support staff development to enhance faculty and staff excellence. This work will introduce and elaborate upon these topics to highlight not only the challenges of the field in a variety of countries worldwide, but to also begin to build comparative understanding of the field at large. In that these institutions are now identified, it is time to academically address their role in higher education.